Endoplasmic Reticulum Stress PERK-ATF4-CHOP Pathway Is Associated with Hypothalamic Neuronal Injury in Different Durations of Stress in Rats - Yi, Shanyong; Shi, Weibo; Wang, He; Ma, Chunling; Zhang, Xiaojing; Wang, Songjun; Cong, Bin; Li, Yingmin (Frontiers in Neuroscience, 2017)
The hypothalamus, which is the initial part of the hypothalamic-pituitary-adrenal (HPA) axis, plays a critical role in regulating stress in the central nervous system. The present study aimed to determine whether endoplasmic reticulum stress in hypothalamic neurons is differentially stimulated by varying durations of stress exposure, which ultimately leads to pathological changes in neurons by affecting HPA axis function. There is a need for better morphological evidence of the mechanisms involved in stress-induced neuron injury. A stress model was established in rats by restraining for 8 h and forced ice-water swimming for 5 min each day. The stress-inducing process lasted for 1 day, 3 days, 7 days, 14 days, and 21 days. Enzyme-linked immunosorbent assay (ELISA) was used to assay serum glucocorticoid levels. Thionine staining was used to observe morphological changes in hypothalamic neurons. Immunohistochemistry and microscopy-based multicolor tissue cytometry (MMTC) was used to detect changes in expression of endoplasmic reticulum stress protein GRP78, ATF4, and CHOP. Serum glucocorticoid levels significantly increased after 3 days of stress exposure and the levels peaked by 7 days. By 21 days, however, the levels were significantly decreased. Thionine staining revealed that prolonged stress exposure resulted in hypothalamic neurons with edema, a lack of Nissl bodies, and pyknotic neurons. Immunohistochemistry and MMTC showed that increasing stress periods significantly decreased GRP78 expression, although ATF4 and CHOP protein expression significantly increased. Stress resulted in pathological changes and significant dynamic changes because of endoplasmic reticulum stress in rat hypothalamic neurons. These results suggested that the endoplasmic reticulum stress PERK-ATF4-CHOP pathway may be associated with hypothalamic neuronal injury.